Prevalence of UTI among Pregnant Women and Its Complications in Newborns - Ranjan, Amit; Sridhar, Srimath Tirumala Konduru; Matta, Nandini; Chokkakula, Sumalatha; Ansari, Rashidah Khatoon (Indian Journal of Pharmacy Practice)
Urinary Tract Infections (UTI) are mainly caused by the presence and growth of microorganisms in the urinary tract, which are the single commonest bacterial infections of all age groups and especially in pregnancy. The main objective of this study is to determine the Prevalence of UTI among pregnant women and complications in their newborns. An observational study was carried out over a period of 6 months. A total of 120 pregnant women were enrolled .UTI was diagnosed based on urinalysis reports. With the help of data collection form demographic data were collected. Out of 120 pregnant women, 35% of them had urinary tract infection. It is mostly observed high in age group of <25yrs, Primigravida, winter season and during Third trimester of pregnancy. The commonest causative organism was found to be E.coli (50%).The weight of newborn infants of mothers afflicted with UTI were significantly not lowered compared to newborns of healthy women. The prevalence rate of urinary tract infection (UTI) during pregnancy is high. So it is important to do routine screening of all pregnant women for significant bacteriuria to reduce the complications on both maternal and fetal health.
Keywords: Urinary Tract Infection; Pregnant women; Newborns; Pyelonephritis; E. coli; multigravida